2021
DOI: 10.1167/iovs.62.12.16
|View full text |Cite
|
Sign up to set email alerts
|

Dual Inhibition of Histone Deacetylases and the Mechanistic Target of Rapamycin Promotes Apoptosis in Cell Line Models of Uveal Melanoma

Abstract: Purpose Over 90% of uveal melanomas harbor pathogenic variants of the GNAQ or GNA11 genes that activate survival pathways. As previous studies found that Ras-mutated cell lines were vulnerable to a combination of survival pathway inhibitors and the histone-deacetylase inhibitor romidepsin, we investigated whether this combination would be effective in models of uveal melanoma. Methods A small-scale screen of inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Effective drug concentrations were selected based on viability assays performed on a panel of uveal melanoma cell lines (Supplementary Fig. S1 ) and a review of relevant literature [ 8 , 13 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Effective drug concentrations were selected based on viability assays performed on a panel of uveal melanoma cell lines (Supplementary Fig. S1 ) and a review of relevant literature [ 8 , 13 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…The selective HDAC1/2 inhibitor romidepsin, a drug approved in cutaneous and peripheral T cell lymphomas, induces cell cycle arrest and apoptosis in solid tumors 14 . Romidepsin is effective in the nanomolar range to induce radiosensitizing effects in lung and bladder tumors, and in combination with mTOR inhibition has been reported to be effective against uveal melanoma 15,16 . Recent reports highlighted the immunomodulatory properties of romidepsin, including the regulation of PD‐L1 expression, associated to modulation of antitumor effects in solid tumors 17 …”
Section: Introductionmentioning
confidence: 99%
“…14 Romidepsin is effective in the nanomolar range to induce radiosensitizing effects in lung and bladder tumors, and in combination with mTOR inhibition has been reported to be effective against uveal melanoma. 15,16 Recent reports highlighted the immunomodulatory properties of romidepsin, including the regulation of PD-L1 expression, associated to modulation of antitumor effects in solid tumors. 17 In our study, we sought to evaluate whether the combination of romidepsin with IFN-α2b, an immunomodulatory cytokine widely used in the past for melanoma treatment 18 could exert antitumor and immunogenic activity against BRAF-mutated melanoma and BRAFi acquired resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Pictilisib (GDC-0941, C23H27N7O3S2, Figure 1) is a potent and selective dual inhibitor of class I PI3K and mTOR and shows favorable pharmacokinetic and toxicological properties when orally administered as a single agent or in combination with chemotherapy agents [17]. Pictilisib is currently undergoing phase II clinical trials for breast cancer [19], ovarian cancer [20], melanoma [21], and multiple myeloma treatment [22]. Clinical studies showed that GDC-0941 has a rapid absorption following oral administration and a dose-proportional pharmacokinetic profile [23].…”
Section: Introductionmentioning
confidence: 99%